A comparative in vitro study on the degree of microleakage in class V cavities using three dentin bonding systems - Sebastian, Arlene C.; Raralio, Gay A.
The marginal integrity and degree of microleakage in class V cavities using 3 dentin bonding systems with their associated composite resin combination (Scotchbond Multipurpose / Z 100 : optibond / Herculite: Prism Universal Bond 3/TPH) were investigated and compared 15 non carious, freshly extracted maxillary premolars stored in NSS were used as samples. A class V cavity was prepared on the buccal surfaces with the occlusal half in enamel end and the other half in cementum. Results showed that all systems exh9ibit microleakage along the enamel restoration interface. Statistical analysis rerveals that there is no significant difference detected in the degree of microleakage among the test samples used. A trend is however, established whereby Scotchbond multipurpose exhibited the least microleakage.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentin-bonding agents; Dental bonding